Adaptation of the Youth Connectedness to Provider scale to assess the relationship between health professionals and adolescent and young adult patients - Gabriela Nogueira Pavan; Luisa F. Roselli; Lilia D'Souza-Li (Elsevier, 2021)
Objective: The aim was to adapt an instrument that evaluates the relationship between young individuals and health professionals to the Brazilian population, which will be called the Escala de Avaliação de Vínculo entre Jovens e Profissionais de Saúde (Youth Connectedness to Provider scale). Method: The questionnaire known as the Youth Connectedness to Provider scale consists of seven Likert-like questions. The translation, back-translation, evaluation by ten specialists, and pre-test with 43 adolescents and young adults aged between 10 and 24 years were performed to assess the clarity and reliability of meanings. The content validity index was calculated for each question. Subsequently, the clinical validation was performed with 83 patients aged 10-24 years old and Cronbach's alpha coefficient was calculated. Results: A content validity index >0.8 (considered satisfactory) was obtained for all items analyzed by experts and adolescents. At the clinical validation, it showed a high internal consistency (Cronbach's alpha = 0.76). The questions showed a good correlation, except for the question about judgment (Spearman's rho = 0.03-0.19). Conclusions: The scale adaptation showed an adequate agreement rate at the translation evaluation and a good reliability index in the questions. This instrument provides information on strengths and topics that require more attention from professionals to improve the relationship with their patients; it can be a valuable parameter in assessing the medical consultation quality.